Hubungan Pembelajaran Toilet Training dengan Kejadian Enuresis pada Anak Prasekolah - Fitriatul Jannah; Lantin Sulistyorini; Dini Kurniawati (UPT Percetakan dan Penerbitan Universitas Jember, 2023)
Preschoolers inclined has many health problem that always threatening and able to impact quality of life such as, general health problems, behavioral disorders, learning disorders, and developmental disorders. One of the health problems in preschool children is enuresis. To overcome this problem can be done by using toilet training to train and teach children to be able to control bowel movements and urinating. The purpose of this study to determine how the relationship of learning toilet training in preschool children (5-6 years) with enuresis in Pakusari District. This study uses quantitative non-experimental analysis that is correlational using a cross-sectional study with the sampling technique Probability Sampling by means of Purposive Sampling and obtained are 252 respondents. Data analysis using Chi Square test. The results (X2 = 21,378; p-value = 0,0001) it can be concluded that there is a relationship between learning Toilet Training in preschool children (5-6 years) with enuresis in Pakusari District. There are several factors that influence learning toilet training such as the environment and education. The family environment is very influential because family has important effect for child. At stage of child growth the parents must attention to see the child’s readiness for receive learning toilet training.